Perancangan Arsitektur Teknologi Informasi Menggunakan Framework TOGAF Pada Koperasi Budi Karya - Arvini Anindhita; Royana Afwani; Ida Bagus Ketut Widiartha (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
This study discusses the design of information technology enterprise architecture in the cooperation of Budi Karya. The main problem encountered is that the management still uses a bookkeeping system. The information obtained in each section has not been integrated with other, the IT management organization structure is not sufficient because there is no staff who have specialized IT experts, and require development in information technology. This was stated in one of the Budi Karya cooperation missions which read "Adopting the development of information technology and modern management systems". This study aims to produce process architecture, data, applications and technology that can be a reference for implementing all activities in cooperation of Budi Karya. This research uses the TOGAF (the Open Group Architecture Framework) which is a framework that has detailed methods and tools for developing and implementing enterprise architecture, with 8 architectural phases of vision, business architecture, information system architecture, technology architecture, opportunities and solutions, migration plan, implementation Governance, and architecture change management. Data collection is done by direct observation interviews and literature studies. The results of all these phases will produce a detailed framework of process architecture, data architecture, application architecture, and architecture in cooperation of Budi Karya Keywords: Enterprise, Architecture, Cooperation, framework, TOGAF